Enhancing Qur'an-Hadith Education through Science, Technology, and Society Approach: A Developmental Study - Rahmiati Rahmiati; M. Zubir; Muhiddinur Kamal; Elfiani Elfiani; Muhamad Rezi; Sofia Ridha (STAI Hubbulwathan Duri, 2025)
This study explores the development of a Qur'an-Hadith learning model incorporating the Science, Technology, and Society (STM) approach to cultivate technological responsiveness and social awareness among Madrasah Tsanawiyah students. The integration of STS is intended to bridge traditional religious education with contemporary societal and technological contexts. A Research and Development (RD) methodology was applied, guided by the McKenney model, which includes the phases of preliminary research, prototyping, and assessment. Each stage was carried out systematically to ensure the validity, practicality, and effectiveness of the proposed model. The STM-based learning model led to notable improvements in student learning outcomes at MTs Sjech Ibrahim Koto Tuo. The model was validated by subject matter experts and demonstrated strong pedagogical relevance. Its practical application in the classroom environment encouraged higher levels of student engagement, creativity, and critical thinking, reflecting a positive shift in students’ technological awareness and social responsibility. Incorporating the STM approach into Qur'an-Hadith instruction enhanced the overall quality and relevance of religious education. This method successfully linked religious content with real-world issues, fostering a more dynamic and contextually aware learning experience. The STM-based learning model presents a promising alternative for Islamic education. Aligning religious studies with scientific and societal dimensions contributes meaningfully to both academic performance and character development among students.